From Criminological Heterogeneity to Coherent Classes: Developing a Typology of Juvenile Sex Offenders - Fox, Bryanna (Youth violence and juvenile justice, 2018)
Although juvenile sex offenders (JSOs) are a pressing topic among researchers and juvenile justice practitioners, empirically driven typologies of JSOs using U.S. data are lacking. Here, we develop the first statistical typology of male and female JSOs using data from the United States selected from a sample of 4,143 JSOs referred to the Florida Department of Juvenile Justice. Significant predictors of juvenile sex offending (age of criminal onset, criminal history, impulsivity, empathy, depression, psychosis, and childhood sexual abuse) derived from the literature were used as grouping covariates to develop a profile of male and female JSOs using a latent class analysis (LCA). Results of the LCA show four unique subtypes of male JSOs and two subtypes of female JSOs exist within the data. These groups had differential compositions for key features such as criminal history and onset, psychopathologies, empathy and impulsivity, and sexual abuse victimization. These differences may be critical toward developing more tailored and effective correctional and treatment responses that balance containment and therapeutic approaches depending on the individual needs of the JSOs based upon their profile. Other practical and theoretical implications of these findings are discussed.